Sensitive detection of strong acidic condition by a novel rhodamine‐based fluorescent pH chemosensor. (15th October 2015) - Tan, Jia‐Lian; Yang, Ting‐Ting; Liu, Yu; Zhang, Xue; Cheng, Shu‐Jin; Zuo, Hua; He, Huawei
Abstract: A novel rhodamine‐based fluorescent pH probe responding to extremely low pH values has been synthesized and characterized. This probe showed an excellent photophysical response to pH on the basis that the colorless spirocyclic structure under basic conditions opened to a colored and highly fluorescent form under extreme acidity. The quantitative relationship between fluorescence intensity and pH value (1.75–2.62) was consistent with the equilibrium equation pH = pKa + log[(Imax – I)/(I – Imin )]. This sensitive pH probe was also characterized with good reversibility and no interaction with interfering metal ions, and was successfully applied to image  Escherichia coli under strong acidity. Copyright © 2015 John Wiley & Sons, Ltd.